The quality of product (smartphone) affecting brand loyalty among STML students in UUM, Sintok - Muhammad Farooq, Fifi Nurfarhana; Othman, Abdul Aziz (Universiti Utara Malaysia, 2020)
The objective of this research is to study the current level of brand loyalty in smartphone purchasing decision among STML students in UUM. Next, this research also investigates the relationship between the quality of product (smartphone) and brand loyalty. Meanwhile, the study also measures the impact of four dimensions of product quality such as performance, feature, reliability and perceived quality on brand loyalty in relation to smartphone purchasing decision. The samples were collected from the students of School of Technology Management & Logistics (STML) in Universiti Utara Malaysia (UUM). The results showed that the current level of brand loyalty in smartphone purchasing decision is highly being influenced by smartphone performance. The relationship between the quality of product (smartphone) and brand loyalty is significant and positive. The four dimensions of smartphone quality which are smartphone performance, smartphone features, smartphone reliability and smartphone perceived quality give an impact on brand loyalty in relation to smartphone purchasing decision. This research will help smartphone companies to generate higher profit as they can give more attention on variable that highly influences brand loyalty among users.